2018
DOI: 10.15829/1560-4071-2018-9-12-16
|View full text |Cite
|
Sign up to set email alerts
|

The specifics of clotting and endogenic fibrinolysis in acute coronary syndrome patients

Abstract: Aim. To assess the processes of clot formation in relation to endogenic fibrinolysis in patients with various types of acute coronary syndrome (ACS).Material and methods. To the study, 89 persons (40 males) included: 59 with ACS, 30 — control group. Among the ACS patients, 28 were ST-elevation (STEMI), 31 with non-ST-elevation ACS (NSTEACS). All participants were assessed for clotting formation parameters and thrombus lysis with rotational elastometry on ROTEM equipment (Germany) and “Hemacore” Thrombodynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Earlier, we demonstrated that the functional state of endothelium as assessed with flow-mediated dilation test (FMD test) correlates with the patency of IRA (11). The higher activity of endogenous fibrinolysis, which is closely interconnected with the functional state of endothelium, is the most probable cause of SR (12)(13)(14)(15). Also, several small studies demonstrated higher platelet reactivity in patients without SR of the IRA (16,17).…”
Section: Introductionmentioning
confidence: 96%
“…Earlier, we demonstrated that the functional state of endothelium as assessed with flow-mediated dilation test (FMD test) correlates with the patency of IRA (11). The higher activity of endogenous fibrinolysis, which is closely interconnected with the functional state of endothelium, is the most probable cause of SR (12)(13)(14)(15). Also, several small studies demonstrated higher platelet reactivity in patients without SR of the IRA (16,17).…”
Section: Introductionmentioning
confidence: 96%